1983
DOI: 10.1021/jo00171a062
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of .beta.-hydroxyglutarohydroxamates to carbapenem precursors

Abstract: loss of the yellow color and filtered while hot to remove the catalyst. Evaporation of the toluene left an oil, which solidified upon cooling. The solid was recrystallized from ethanol to give 50 mg (28%) of 2-ethylanthracene, mp 148-150 °C (lit.13 mp 148-150 °C). A mixed melting point with authentic 2-ethylanthracene was not depressed.Diels-Alder Reactions of Anthra[2,3-6 Jthiophene. 5,thiophene (11). Among several attempts to prepare dicyanoacetylene by published methods, the one reported by Byrd and co-work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In fundamental research, efficient biomimetic methods for b-lactam syntheses were developed based on the intramolecular N-alkylation of b-hydroxyalkoxamates derived from amino acids. [42][43][44][45] In contrast, recent studies have revealed that competitive O-alkylation occurs in several cases with amides and carbamates. [46][47][48][49][50][51][52] We have therefore investigated the intramolecular cyclization of d-hydroxyalkoxamates derived from d-glycono-1,5-lactone under Mitsunobu conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In fundamental research, efficient biomimetic methods for b-lactam syntheses were developed based on the intramolecular N-alkylation of b-hydroxyalkoxamates derived from amino acids. [42][43][44][45] In contrast, recent studies have revealed that competitive O-alkylation occurs in several cases with amides and carbamates. [46][47][48][49][50][51][52] We have therefore investigated the intramolecular cyclization of d-hydroxyalkoxamates derived from d-glycono-1,5-lactone under Mitsunobu conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for the synthesis of 3,4-disubstituted β-lactams are now available. In particular, the addition of imines to ketenes 4 or to ester enolates 5 has acquired significant importance for the asymmetric synthesis of the azetidinone ring. 1a, Alternatively, precursors from the “chiral pool” for the synthesis of β-lactams are, for example, β-amino acids, β-amino esters, β-halo amides, and β-hydroxy amides . However, methods for the construction of β-lactams with quaternary stereogenic centers are still scarce.…”
Section: Introductionmentioning
confidence: 99%